Roles of Community Psychiatric Nurses for Enhancing Resilience in Caregivers of First Diagnosed Schizophrenic Patients - Nilati , Julaluck; Singsanun , Naovarat (Journal of Nursing, Siam University, 2022)
Resilience is a force that represents a person’s ability to face critical or difficult situations. This can be able to adapt and recovery to normal. It is a vital force for caregivers for first-illness schizophrenic patients. Because schizophrenia is a disorder characterized by inappropriate thinking, perception, behavior and mood. They have a very different appearances and limited of ability to perform any functions. This makes it a burden for the caregivers, specifically in the case of the first diagnosed. The caregiver who lacked experience in caring for a schizophrenia patient may face many effects such as stress and high anxiety. In long term, they may affect their mental health such as tiredness, discouragement, or pessimism, and inappropriate emotional management including serious mental consequences. The community psychiatric nurses’ role was helping patients, caregivers, families and communities. The objectives of this article will present the roles of community psychiatric nurses in mental health care and resilience enhancement for caregivers who were caring for first diagnosed schizophrenic patients to have the knowledge and understanding of schizophrenic patients. The caregiver can take care of themselves and have the resilience, can be dependable for schizophrenia patients.